2012
DOI: 10.1038/cr.2012.166
|View full text |Cite
|
Sign up to set email alerts
|

Recapitulation of spinal motor neuron-specific disease phenotypes in a human cell model of spinal muscular atrophy

Abstract: Establishing human cell models of spinal muscular atrophy (SMA) to mimic motor neuron-specific phenotypes holds the key to understanding the pathogenesis of this devastating disease. Here, we developed a closely representative cell model of SMA by knocking down the disease-determining gene, survival motor neuron (SMN), in human embryonic stem cells (hESCs). Our study with this cell model demonstrated that knocking down of SMN does not interfere with neural induction or the initial specification of spinal motor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 45 publications
(73 reference statements)
4
51
1
Order By: Relevance
“…In addition, the TUJ1-positive FB cells derived from ADAR1 KD H9 cells exhibited much shorter growing neurites at all differentiation stages ( Figure 1F). Meanwhile, although the differentiation efficiency of MNs was only about 30%-40% as reported previously [37], we found that ADAR1 knockdown also dramatically repressed the formation of MN clusters ( Figure 1H) and HB9-positive MNs ( Figure 1I). The resulting MNs also exhibited a significant reduction of neurite outgrowth ( Figure 1I).…”
Section: Hescs Lacking Adar1 Exhibited Significant Defects In Eb Formmentioning
confidence: 48%
See 4 more Smart Citations
“…In addition, the TUJ1-positive FB cells derived from ADAR1 KD H9 cells exhibited much shorter growing neurites at all differentiation stages ( Figure 1F). Meanwhile, although the differentiation efficiency of MNs was only about 30%-40% as reported previously [37], we found that ADAR1 knockdown also dramatically repressed the formation of MN clusters ( Figure 1H) and HB9-positive MNs ( Figure 1I). The resulting MNs also exhibited a significant reduction of neurite outgrowth ( Figure 1I).…”
Section: Hescs Lacking Adar1 Exhibited Significant Defects In Eb Formmentioning
confidence: 48%
“…At 10 and 17 days of neural differentiation, hESC-derived primitive and definitive neuroepthelial (NE) cells with scramble shRNA treatment presented typical columnar NE morphology and were organized into rosettes [36][37][38] (Figure 1D and 1E), similar to the structure of NE cells from WT hESC induction (as discussed below and data not shown). Noticeably, although differentiating hESCs with stable ADAR1 knockdown also formed rosette-like structures, these cells expressed low levels of PAX6, SOX1 and FOXG1 ( Figure 1D and Supplementary information, Table S1), and formed much Table S1.…”
Section: Hescs Lacking Adar1 Exhibited Significant Defects In Eb Formmentioning
confidence: 68%
See 3 more Smart Citations